2010
DOI: 10.1021/jf902689j
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Novel Nitromethylene Neonicotinoids with Tetrahydropyridine-Fixed Cis Configuration in Aqueous Solution

Abstract: Photodegradation of 1-((6-chloropyridin-3-yl)methyl)-7-methyl-8-nitro-1,2,3,5,6,7-hexahydroimidazo[1,2-a]pyridin-5-ol (IPPA152001) and 1-((6-chloropyridin-3-yl)methyl)-7-methyl-8-nitro-5-propoxy-1,2,3,5,6,7-hexahydroimidazo[1,2-a]pyridine (IPPA152004) was studied in distilled water; high-pressure mercury lamp and xenon lamp were used as light sources. The photolytic rate constants of the two compounds and their half-lives were calculated. Compared with imidacloprid, the order of photodegradation rate of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 24 publications
7
35
0
1
Order By: Relevance
“…The fragmentation pattern for M5 was similar to the photodegradation product 8-carbonyl-derivative as reported by Zhao et al 30 Therefore, M5 was tentatively identified as 1-((6-chloropyridin-3-yl)methyl)-7-methyl-5-propoxy-8-carbonyl-hexahydro-imidazo[1,2-a]pyridine.…”
Section: ■ Results and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The fragmentation pattern for M5 was similar to the photodegradation product 8-carbonyl-derivative as reported by Zhao et al 30 Therefore, M5 was tentatively identified as 1-((6-chloropyridin-3-yl)methyl)-7-methyl-5-propoxy-8-carbonyl-hexahydro-imidazo[1,2-a]pyridine.…”
Section: ■ Results and Discussionsupporting
confidence: 77%
“…For instance, M1 was found as a product of IPP in aqueous solution after irradiation with a mercury and xenon lamp. 30 In addition, M1 was shown to have activity against insect pests. 37 Similarly, metabolites of imidacloprid derived from treated plants were observed to be highly toxic to aphids.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Paichongding (IPP, 1-((6-chloropydidin-3-yl) methyl)-7-methyl-8-nitro-5propoxy-1,2,3,5,6,7-hexahydroimidazo[1, 2-α-]-pyridine) is a novel nitromethylene neonicotinoid recently developed by the East China University of Science and Technology in China (Zhao et al 2010;Fu et al 2013a, b;Li et al 2013;Wang et al 2013;Zhang et al 2013;Cai et al 2015b). IPP is different from the traditional neonicotinoids as it is the antagonist of the postsynaptic nicotinic acetylcholine receptors (nAChRs) of insects.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have mainly focused on its photodegradation in aqueous solution, translocation in Youdonger (Brassica campestris subsp. Chinensis, Chinese cabbage), IPP metabolism, extractable and bound residue, and transformation in soils (Zhao et al 2010;Fu et al 2013a, b;Li et al 2013;Wang et al 2013;Zhang et al 2013;Cai et al 2015b, c). The effect of IPP on soil microbial communities in aerobic soils has not been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…Ecust stellte IPPA152004 (98) vor, das gegen imidaclopridresistente Reiszikaden wirkt. Das Produkt soll unter dem Namen Paichongding in China vermarktet werden 130. In den letzten Jahren verschwanden einige ältere Produkte zur Bodenbehandlung vom Markt.…”
Section: Highlights Aus Der Agrochemieunclassified